Quality Risk Management In The Pharmaceutical Industry: A Literature Review - Aditya Naufal Maulana; Hari Restu Putra Martam Murad; Dyah Mashita Nur Hanan Rahim; Mohamad Aprianto Paneo; Multiani S. Latif (International Journal of Health Engineering and Technology, 2026)
Quality Risk Management (QRM) is increasingly recognized as a critical framework for ensuring pharmaceutical product quality, safety, and regulatory compliance throughout the product lifecycle. This literature review aimed to examine the implementation of QRM in the pharmaceutical industry, with a particular focus on its role in preventing deviations and quality failures. A total of 25 scientific articles published between 2020 and 2026 were systematically collected and analysed from databases including Google Scholar, ScienceDirect, PubMed, and ResearchGate using predefined inclusion and exclusion criteria. The results indicate that QRM tools — particularly Failure Mode and Effect Analysis (FMEA), Corrective and Preventive Action (CAPA), Quality by Design (QbD), and risk matrices — are widely applied across manufacturing, supply chain, warehousing, packaging, and distribution processes. FMEA was identified as the most prevalent risk assessment method, while integrated CAPA systems have demonstrably shifted quality management from a reactive to a proactive paradigm. Challenges including subjectivity in risk scoring, limited training, and suboptimal integration with quality management systems remain prevalent. This review concludes that comprehensive QRM implementation significantly reduces the frequency of deviations, strengthens GMP compliance, and enhances patient safety in the pharmaceutical industry.